1969
DOI: 10.1111/j.1699-0463.1969.tb04219.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Sensitivity of the Rhodamine B Method for Keratinization by the Use of Fluorescent Light

Abstract: Rhodamine B was first used as a stain for cornification b y Adortinofti 1924, who presented two methods for eleidine and keratogenc substances i n which the dye was used together with either monophenylrosanilin o r Victoria blue. I n 1968, Liisberg published a method for demonstrating-cornified tissue which mas claimcd to he extremcly specific. Rhodamine H was uscd a t pH 3,6 after blocking of basophilic suhstances by toluidine blue.The present authors tried Liisberg's method on formalin fixed, paraffin embedd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1971
1971
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Strong reaction in parakeratinized KCOTs suggested an alteration in gene expression that is also observed in BCCs but not in normal tissues and it was felt that this might support the view that the OKC (KCOT) had neoplastic potential. 28 Another study 29 showed similar results and suggested GP38 can be used to differentiate between the two varieties (parakeratinized and orthokeratinized). It has been suggested that whenever, there is loss of classic features of KCOTs due to inflammation this molecule may play a diagnostic role and differentiate aggressive (parakeratinized) and less aggressive (orthokeratinized) KCOTs.…”
Section: Antigenic Expressionsupporting
confidence: 55%
“…Strong reaction in parakeratinized KCOTs suggested an alteration in gene expression that is also observed in BCCs but not in normal tissues and it was felt that this might support the view that the OKC (KCOT) had neoplastic potential. 28 Another study 29 showed similar results and suggested GP38 can be used to differentiate between the two varieties (parakeratinized and orthokeratinized). It has been suggested that whenever, there is loss of classic features of KCOTs due to inflammation this molecule may play a diagnostic role and differentiate aggressive (parakeratinized) and less aggressive (orthokeratinized) KCOTs.…”
Section: Antigenic Expressionsupporting
confidence: 55%
“…It is also known, like other dyes from the xanthenes family, to possess high fluorescent properties . In this work, we used it as a fluorochrome . Under UV light, the high intensity of fluorescent is detected in the epidermis.…”
Section: Resultsmentioning
confidence: 99%